1996
DOI: 10.1007/bf00417901
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bolus volume and viscosity on anterior lingual force during the oral stage of swallowing

Abstract: The influence of bolus volume and viscosity on the distribution of anterior lingual force during the oral stage of swallowing was investigated using a new force transducer technology. The maximum force amplitudes from 5 normal adults were measured simultaneously at the mid-anterior, right, and left lateral tongue margins during 10 volitional swallows of 5-, 10-, and 20-ml volumes of water, applesauce, and pudding. Results indicated significant increases in peak force amplitude as viscosity increased. Volume di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(88 citation statements)
references
References 20 publications
5
81
2
Order By: Relevance
“…Previous studies of the effects of bolus volume on tongue pressure during swallowing also emphasized that bolus volume affected neither peak amplitude nor duration of tongue pressure (29,30), perhaps because the total number of swallows increased with increasing volume and with the number of squeezes until first swallow.…”
Section: Effects Of Bolus Characteristics On Tongue Pressure During Smentioning
confidence: 99%
“…Previous studies of the effects of bolus volume on tongue pressure during swallowing also emphasized that bolus volume affected neither peak amplitude nor duration of tongue pressure (29,30), perhaps because the total number of swallows increased with increasing volume and with the number of squeezes until first swallow.…”
Section: Effects Of Bolus Characteristics On Tongue Pressure During Smentioning
confidence: 99%
“…Thickening agents may promote safer swallowing as they lower the risk of aspiration (Kuhlemeier et al, 2001). Compared to thin liquids, thickened liquids are associated with higher values of some swallowing parameters, such as the total swallowing duration (Chi-Fishman and Sonies, 2002), number of swallowing movements (Hamlet et al, 1996), and peak lingual force amplitude (Miller and Watkin, 1996); however, the range of liquid viscosity suitable for dysphagic patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Thickening agents may promote safer swallowing as they lower the risk of aspiration (Kuhlemeier et al, 2001). Compared to thin liquids, thickened liquids are associated with higher values of some swallowing parameters, such as the total swallowing duration (Chi-Fishman and Sonies, 2002), number of swallowing movements (Hamlet et al, 1996), and peak lingual force amplitude (Miller and Watkin, 1996); however, the range of liquid viscosity suitable for dysphagic patients remains unclear.In Japan, thickeners in a dry mix powder form are used to provide instant viscosity to liquids, and the products formed are called "TOROMI". Although Japanese people favor thinner liquids, clinical staff prepare thicker TOROMI to prevent aspiration in dysphagic patients; however, they are often unsure how to adjust the liquid consistency for each individual dysphagic patient.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that ragi (0.47-0.51) and wheat (0.55-0.58) Halubai samples had higher adhesiveness compared to rice (0.21-0.22) samples. In other words, ragi and wheat samples required comparatively more work (mastication) when these samples were manipulated in the mouth between the molars (Miller and Watkin 1996).…”
Section: Texturementioning
confidence: 99%